ANTESEDEN PENGUNGKAPAN LINGKUNGAN DAN PENGARUHNYA TERHADAP IMAGE PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur di Indonesia) - Aziza, Nurna (JURNAL FAIRNESS, 2014)
This study aims to test models of the antecedents of environmental disclosure and effect environmental disclosure on corporate image, is to analyze the factors to be driving to the disclosure of environmental management and the consequences for the management of the company after the disclosure environment. Analysis of the factors to be driving to the disclosure of environmental management include: stakeholders force, environmental regulation (command-and-control regulation and voluntary normative regulation) and environment commitment. The research was based on the Theory of Legitimacy. The data was collected through questionnaires in accounting and department director in charge of the environment or the manufacturing company that went public in Indonesia Stock Exchange as many as 149 companies. Data of financial statements and annual report are also used to study the environmental disclosure and financial performance. The 447 questionnaires distributed, 141 which can be used in the analysis with a response rate of 31.54%. Data analysis using structural equation models with the help of the program AMOS version 20/IBM. Test results showed that stakeholders force does not have a positive in the environmental disclosure, environmental regulation (command-and-control regulation and voluntary normative regulation) does not have a positive effect on environmental disclosure and environmental commitment has a positive effect on environmental disclosure. Disclosure environment has a positive effect on corporate image.